STUDENTS’ STRATEGIES IN ACADEMIC WRITING: A STUDY ON LEARNING STRATEGIES USED BY HIGH-ACHIEVEMENT STUDENTS AT STKIP MUHAMMADIYAH BONE - Syamsir Bin Ukka; Baso Jabu; Sukardi Weda (Pascasarjana IAIN Sorong, 2019)
This research aimed to find out the strategies used by the high-achievement students in academic writing and to find out the lecturers’ perception about the strategies applied by the students at STKIP Muhammadiyah Bone. This research is a descriptive qualitative research that applied two research questions. The data was collected from the subjects that consist of six students and one lecturer. The research subjects were chosen by purposive sampling technique. The researchers were the main instruments of the research and applied interview and taking research notes by using observation sheets. This research used interview and observation to collect the data. The writing class activities were observed and the respondents were interviewed. The results were analyzed descriptively. Based on the data analysis, it was found that students used different learning strategies in academic writing. Students A and C used cooperative learning strategy because they enjoyable in small group discussions before make decision while Students B and E used mapping strategy who like follow the structured writing stage of writing. Student D used spider web strategy that refers to arrange the ideas more structured and Student F used collaborative learning strategy that student who like giving and asking help. The lecturer’s perception indicated that students who learnt writing skill use different strategies based on their understanding level. The findings and conclusions noted that the learning strategies applied by the students in this research based on their achievement level and learning style. By these strategies, the students are capable to increase their writing skill by using the appropriate strategy.